F(r)- f(r+dr)= r*k*dr, df(r)= f(r+dr)- f(r), and the original formula can be changed to-DF (R)/DR = R * K.
Then f(r)= (-k*r*r/2)+ C can be obtained by indefinite integration, where c is a constant. And because f(L)= 0, it is substituted.
C=k*L*L/2, substitute W*W*M/L=k to get f (r) = (-w * w * m * r/2l)+(w * w * m * l/2).
Finally, substitute r=R and get the answer f(R)=(W*W*M*L/2)-(W*W*M*R*R/2L).
The tension in the problem exists between every two short pieces of rope and exists in pairs. The two Zhang Liwei interaction forces of each pair provide centripetal force for each short piece of rope.